Becoming Like Creoles : Living and Leading at the Intersections of Injustice, Culture, and Religion - DeYoung, Curtiss Paul; Ka'ai, 'Iwalani; Garcia, Sindy Morales; Nahar, Sarah Thompson; Afrik, Robyn; Jones, Micky ScottBey; Lewis, Jacqueline J. (Book collections on Project MUSE., 2019)
The French Caribbean authors of In Praise of Creoleness (Éloge de la Creolite) exclaim, "Neither Europeans, nor Africans, nor Asians, we proclaim ourselves to be Creoles." Creoleness, therefore, becomes a metaphor for humanity in all its diversity. Unique among the many images useful for discussing diversity, Creoleness is formed within a history of injustice, oppression, and empire. Creolization offers a way of envisioning a future through the interplay between cultural diversity, injustice and oppression, and intersectionality. People of faith must embrace such metaphors and practices to be relevant and effective for ministry in the 21st century. Using biblical exposition in conversation with present day Creole metaphors and cultural research, Becoming Like Creoles seeks to awaken and prepare followers of Jesus to live and minister in a world where injustice is real and cultural diversity is rapidly increasing. This book will equip ministry readers to embrace a Creole process, becoming culturally competent and social justice focused, whether they are emerging from a history of injustice or they are heirs of privilege.